Prostate cancer - the role of magnetic resonance imaging - Móciková, Ingrid; Babeľa, Jozef; Baláž, Vladimír (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2012)
BACKGROUND: This article reviews the potential of magnetic resonance imaging (MRI) in prostate cancer diagnosis. METHODS: Systematic scan of Pubmed, Ovid, Medline, Elsevier search engines was used, additional information was found through bibliographic review of relevant articles. Results. Substantial progress has been made in the imaging of prostate cancer in MR imaging, as well as in advanced MR spectroscopy. CONCLUSIONS: MRI is a non-invasive and direct imaging modality useful for cancer staging, therapy response, detection of recurrence and guided biopsy in previous negative biopsies. MRI with 3.0T system, whole-body MRI, dynamic contrast enhanced MRI, diffusion-weighted imaging (DWI) and MR spectroscopy (MRS) have improved tumor staging, assessment of tumor volume, aggressiveness or recurrence. Implementation of endorectal/phased array superficial MRI findings on 1.5 or 3.0T systems into nomograms for prostate pretreatment prediction is warranted. Surface phasedarray coil MRI accurately defines prostate cancer with elevated risk of extraprostatic disease.
Keywords: mužské pohlaví; Lymph Nodes; semenné váčky; Seminal Vesicles; Lymphatic Metastasis; Male; Magnetic Resonance Imaging; lidé; nádory prostaty; lymfatické metastázy; Humans; magnetická rezonanční tomografie; Prostatic Neoplasms; lymfatické uzliny